Des livrets d'accueil pour enseigner le français aux réfugiés - Karima Gouaïch; Marie-Noëlle Roubaud; Brahim Azaoui (Université de Provence, 2019)
This paper provides reflexive thoughts on the experimentation of welcome guides for adult migrants that were developed within the Erasmus+ Xenios Zeus project. The retrospective analysis underlines the interest of experimentations to make the structure and content of the material evolve so as to correspond to the needs of the targeted public. The experimentation took place in two associations and with 31 adult migrants. The implementation made it possible to collect the trainers' conceptions of teaching French as a foreign language to this public, which includes a strong social and civic dimension. On the migrants' side, the use of the guides brings out a tension in the relationship to French and to France, sometimes far from the ideal representation imagined before migration. This tension, and in particular the negative view of the current reality, is probably linked to several socio-political factors such as the feeling of social downgrading experienced by some participants. The analysis of the migrants' discourse enabled remediations to the welcome guides, notably regarding the place of literacy and contextualization.